ANALYSIS OF EXPORT COMPETITIVE POWER OF INDONESIA'S FARMING OF COMMODITIES IN ASEAN COUNTRIES - Hardin, Hardin (Pascasarjana Universitas Halu Oleo, 2016)
This study aims to (1) To analyze and determine the Indonesia's competitive power of export of commodities in the sub sector of farming among ASEAN countries; (2) To analyze and determine the types of commodities that can be used as an export commodity specialization Indonesian in farming sector. Object of this research is secondary data that the data exports of commodities in the sub sector of farming in ASEAN countries and world in aggregates in the product classification (HS Code) 6 digits in the unit of measure US Dollar with the study period 2011-2014. Techniques of data collection is done through the study of literature by means of browsing or downloading via the website address of the institution http://www.trademap.org/Product_SelCountry TRADE MAP International (Trade statistics for International Business Development). The method used is the analysis by using the Revealed Comparative Advantage (RCA) and Comparative Export performace (CEP). Results of the analysis showed that the export competitive power of Indonesiaâ€™s farming sub-sector commodity to countries other ASEAN, 15 kinds of commodities studied, there are 9 types of commodities that have competitive power, namely RCA potatoes with an average of 2.62; RCA sweet potato an average of 1.80; RCA cashew nut shells, an average of 5.67; RCA coffee with an average of 1.80; RCA turmeric average 3.18; RCA copra with an average of 3.81; RCA palm oil with 4.04; cocoa beans with an average of 4.61 RCA and RCA tobacco with an average of 2.22. Indonesia and competitiveness of the world shows that of the 15 types of commodities that are analyzed are 8 types of commodities that can be used as an export commodity specialization namely CEP sweet potato with an average of 2.96; CEP cashew nut shells, an average of 4.07; CEP coffee with an average of 5.13; CEP pepper on average 2.01; CEP copra with an average of 21.71; CEP palm oil with an average of 49.55; cocoa beans with an average of 4.27 CEP and CEP rubber with an average of 1.92. Keywords: Competitive Power, Export, Commodities In The Farming Sub-Sector. Â